تأثير شدة التقليم في إنتاج وجودة ثمار الحمضيات صنف أبو صرة - ديب علي; بلال عصام (Latakia University Journal -Biological Sciences Series, 2018)
The study was carried out at Boqa center for research and plant production of the Faculty of Agriculture at Tishreen University, in citrus orchard (Washington navel), total area of 4 dunums During the year 2016 on trees 12 years old and planted with (5*5) m spacing and grafted on citrus aurantium root stock. The experiment was designed in randomized block way, and included four treatments with three replications and two trees in each replication: control (A): Remove water sprout, diseased, dry, broken and congested branches. light pruning (B): (Remove 10-15% of branches last year + control). Medium pruning (C): (Remove 16-20% of branches last year + control). heavy pruning (D): (Remove 21-25% of branches last year + control). The study showed the following results: * The Treatment of heavy pruning was superior total sugars (8.20%), maturation factor (10.9),and Total soluble solids(11.5%). * The Treatment of heavy pruning was superior percentage of contract (20.3%), size and weight of fruit (254.2 g ,282.9 cm3) , and average weight of juice (388.2 g juice/kg fruit) . * The treatment of heavy pruning gave the lowest percentage of total acidity (1.1%), and gave the highest value to the fruit content of the vitamin C (40.1mg/100ml juice). نفذت الدراسة في مركز بوقا للبحوث والإنتاج النباتي التابع لكلية الزراعة بجامعة تشرين في بستان حمضيات صنف أبو صرة، مساحته الإجمالية / 4 / دونم خلال العام 2016 م, على أشجار بعمر 12 سنة, مزروعة بمسافات (5×5) م ومطعمة على أصل النارنج. صممت التجربة بطريقة القطاعات العشوائية؛ إذ تضمنت أربع معاملات وثلاث مكررات للمعاملة وشجرتين لكل مكرر: الشاهدA : إزالة الطرود والفروع المائية والفروع المريضة والجافة والمتكسرة والمتزاحمة. تقليم خفيف B: ( إزالة10 - % 15من نموات العام الماضي + الشاهد). تقليم متوسطC : ( إزالة 16-20 % من نموات العام الماضي+ الشاهد). تقليم شديدD : (إزالة 21-25% من نموات العام الماضي+ الشاهد ). أظهرت الدراسة النتائج الآتية: v تفوقت معاملة التقليم الشديد على باقي المعاملات بنسبة السكريات الكلية (8.20%) ومعامل النضج (10.9) ونسبة المواد الصلبة الذائبة الكلية (%11.5). v تفوقت معاملة التقليم الشديد في نسبة العقد (%20.3) ووزن وحجم الثمرة (254.2 غ , 282.9 سم3), وكذلك في متوسط وزن العصير (388.2 غ عصير/كغ ثمار). v أعطت معاملة التقليم الشديد أدنى قيمة للحموضة الكلية (1.1%) وأعلى قيمة لمحتوى الثمار من فيتامين C (40.1 ملغ /100 مل عصير).